THE EFFECTIVENESS COMBINATION OF RESISTANT VARIETIES AND METALAXIL FUNGICIDE IN CONTROLLING DOWNY MILDEW DISEASE (PERONOSCLEROSPORA MAYDIS) IN MAIZE PLANT - Pakki, Syahrir; Djaenuddin, Nurasiah (Universitas Lampung, 2019)
Downy mildew caused by Peronosclerospora maydis is an important disease in the centers of corn cultivation in Java. The aim of this study was to determine the effectiveness of a combination of metalaxyl fungicide and varieties that have a high sustainability of downy mildew caused by P. maydis. The study was conducted in Kediri, East Java, which is an endemic area of downy mildew caused by P. maydis. The Split Plot Design with 3 replications was used in this study. The main plots were 5 corn varieties (1) Bima-3 Bantimurung, (2) Bima-20 URI, (3) Lagaligo, (4) Bima-15 Sayang, and (5) Anoman as a susceptible check. The subplots were 5 levels of seed treatment dose with metalaxyl fungicide (0 g/kg, 2 g/kg, 3 g/kg, 5 g/kg, and 7 g/kg seeds). The combination of resistant varieties with metalaxyl at a dose level of 5 g and 7 g/kg of corn seeds was effective in controlling downy mildew caused by P. maydis. In Bima-3 varieties Bantimurung and Lagaligo showed low infection reactions of 7.7-8.1%, and 10.4?11.2% respectively. In a combination of treatment conditions of susceptible varieties (Anoman) with 2, 3, 5 and 7 g/kg seeds, disease incidence reach 100% or most of the plants die. The lower incidence was also followed by yield, ear length and weight of a 1000 seeds that higher than other treatments. The combination of the use of susceptible variety with 2 g to 7 g/kg of metallaxyl doses was not effective in controlling downy mildew caused by P. maydis.